Primary cutaneous leiomysarcoma - Shubhangi Vinayak Agale; Sumit Grover; Rahul Zode; Shilpa Hande (Wolters Kluwer Medknow Publications, 2011)
Primary cutaneous leiomyosarcoma of the skin is a rare soft tissue neoplasm, accounting for about 2-3% of all superficial soft tissue sarcomas. It arises between the ages of 50 and 70 years, and shows a greater predilection for the lower extremities. Clinically, it presents with solitary, well-circumscribed nodule and, microscopically, consists of fascicles of spindle-shaped cells with "cigar-shaped" nuclei. Local recurrence is known in this tumor. We document a case of primary cutaneous leiomyosarcoma in a 77-year-old man and discuss the histological features and immunohistochemical profile of this uncommon neoplasm.